No change in network connectivity measurements between separate rsfMRI acquisition times - Neal, Elliot G.; Schimmel, Samantha; George, Zeegan; Monsour, Molly; Alayli, Adam; Lockard, Gavin; Piper, Keaton; Maciver, Stephanie; Vale, Fernando L.; Bezchlibnyk, Yarema B. (Frontiers in Network Physiology, 2024)
The role of resting state functional MRI (rsfMRI) is increasing in the field of epilepsy surgery because it is possible to interpolate network connectivity patterns across the brain with a high degree of spatial resolution. Prior studies have shown that by rsfMRI with scalp electroencephalography (EEG), an epileptogenic network can be modeled and visualized with characteristic patterns of connectivity that are relevant to both seizure-related and neuropsychological outcomes after surgery. The aim of this study is to show that a five-minute acquisition time provides reproducible results related to the relevant connectivity metrics when compared to a separately acquired five-minute scan. Fourteen separate rsfMRI sessions from ten different patients were used for comparison, comprised of patients with temporal lobe epilepsy both pre- and post-operation. Results showed that there was no significant difference in any of the connectivity metrics when comparing both five-minute scans to each other. These data support the continued use of a five-minute scan for epileptogenic network modeling in future studies because the inter-scan variability is sufficiently low as not to alter the output metrics characterizing the network connectivity.